Revitalisasi Nilai-nilai Moral Keagamaan dalam Merespon Realitas Zaman - Saleh, Fauzan (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
Indonesia has been developed in a various ways. But there remains one field in which this country has been kept captive of, namely the field of morality. Morally speaking, the country is not improving, nor is it heading toward the right direction. It is even regressing. The regress of proper moral virtue has made this country lost its very identity and hope. The situation is worsened by the fact that the schools and universities that are supposed to play the central role in moral education have not been effective either. Religion has been presented wrongly simply as a belief system. Its aspect as moral system is partly or completely ignored. This paper is an attempt to explore this abandoned precious dimension of religion and its importance in the process of moral education. We assume that it is only through religion, to be more precise through inacting the religous morality that we can cure the social malayses, and move on with our aspiration and hope.